Raffaele Riario, Jacopo Galli, and Michelangelo’s Bacchus, 1471–1572 - Christian, Kathleen W. (Brepols, 2024)
On Michelangelo’s first day in Rome, in June 1496, Cardinal Raffaele Riario asked him if he could create ‘something beautiful’ in competition with the antique. The twenty-one-year old sculptor responded to this unique challenge with the statue of <span class=